Development of biodegradable conductive cotton yarns by in-situ polymerisation of pyrrole. Issue 1 (2nd January 2019) - Datta, Mallika; Chaudhuri, Atin; Mitra, Mainak; Nath, Devarun; Das, Debasish
Abstract: Cotton yarns were modified with pyrrole in the presence of ferric chloride following a dip-nip-dry technique. Treatment of cotton with 23.4% aqueous pyrrole followed by treatment with 40.6% aqueous ferric chloride and subsequent drying in atmospheric air produced balanced improvements in the properties of the yarn such as conductivity, tensile strength and extensibility. Among the three types of yarns such as ring spun, rotor spun and friction spun considered for such treatment, ring spun yarn performed best in respect of conductivity and retention of strength. Examination of surface morphology of yarns by scanning electron microscopy revealed a common discontinuity in the growth of polypyrrole along the length of the yarns spun using friction spinning and rotor spinning systems. Such discontinuity was caused by the wrapper fibres. Ring spun yarn, on the other hand, allowed a continuous spiral growth and deposition of polypyrrole in the inter-fibre space and on the surface of the yarn. Study of pyrrole modified ring spun yarn in a typical photoluminescence system indicated photoluminescence property of such pyrrole-treated cotton yarn.